2014
DOI: 10.1002/jcb.24874
|View full text |Cite
|
Sign up to set email alerts
|

Verrucarin A induces apoptosis through ROS-mediated EGFR/MAPK/Akt signaling pathways in MDA-MB-231 breast cancer cells

Abstract: The present study was carried out to elucidate the mechanisms underlying Verrucarin A (VA)-induced cytotoxicity in human breast cancer cell line MDA-MB-231. VA inhibited the growth of MDA-MB-231 cells by induction of reactive oxygen species (ROS)-dependent mitochondrial apoptosis. Elevation of ROS production, associated with changes in Bax/Bcl-2 ratio, led to loss of mitochondrial membrane potential (Δψm) and cytochrome c release in VA-treated cells. Release of cytochrome c from mitochondria to cytosol trigger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 21 publications
(25 reference statements)
3
23
0
Order By: Relevance
“…Moreover, evidence from earlier studies show that there seems to be a hierarchy in the relationship between ROS and Akt, in which ROS tends to function as an upstream signal for Akt [24,45,46]. In the current study, we demonstrated for the first time that both the activity of PI3k/Akt pathway and the cellular redox state are closely related to the pharmacological effect of Deguelin.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Moreover, evidence from earlier studies show that there seems to be a hierarchy in the relationship between ROS and Akt, in which ROS tends to function as an upstream signal for Akt [24,45,46]. In the current study, we demonstrated for the first time that both the activity of PI3k/Akt pathway and the cellular redox state are closely related to the pharmacological effect of Deguelin.…”
Section: Discussionsupporting
confidence: 62%
“…As previously reported, tumor cells are vulnerable to the induced ROS generation due to the insufficiency of antioxidant mechanisms [24,27]. Intracellular ROS accumulation by some chemotherapeutics is one of the most important strategies of inducing the apoptosis of cancer cells [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…p38MAPK and ERK are two important proteins in the MAPK pathway, and MAPK/AKT has been associated with multiple kind of cancers by modulating tumor cells proliferation, apoptosis, and metastasis [30-32]. Similar, Wnt/β-Catenin has also been reported as a pivotal regulator of tumor cells metastasis [33-35].…”
Section: Discussionmentioning
confidence: 99%
“…70,71 However, fewer reports describe p38- or JNK-mediated signaling as part of the molecular mechanism of drug-induced DNA damage. 1,21 We and others have previously demonstrated a link between AhR signaling and the ability of 5F 203 to mediate DNA damage.…”
Section: Discussionmentioning
confidence: 99%